Akibat Hukum Tidak Terlaksananya Hak Asuh Anak Pasca Perceraian Orang Tua Di Pengadilan Agama Gorontalo - Muhamad Nur Rifaldi Rachman; Nirwan Junus; Julius T. Mandjo (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
This research aims to find out what child custody rights are like after parents' divorce in the Gorontalo Religious Court and what the legal consequences are for child custody after parents' divorce. The method used in this research uses a normative type of research. This research uses a comparative approach (Comparative Approach) and a fact approach (The Factapproach). The results of this research found that divorce between husband and wife has a big impact, especially on child custody rights after parental divorce with an approach from the perspective of Islamic law and the Constitution. Law Number 1 of 1974 concerning Marriage. The Gorontalo Religious Court's decision regarding child custody is also a supporting factor, highlighting the best interests of the child as the main priority. Interviews with Gorontalo Religious Court Judges show that the court's adaptation to modern family dynamics and the involvement of children in the decision-making process is in the spotlight. In concrete cases, the research describes two decisions related to child custody, highlighting the importance of considering casuistry and the best interests of the child in making custody decisions. This research seeks to provide a holistic and sensitive picture of the complexity of child custody cases with a focus on child welfare as the main priority. Divorce between husband and wife raises responsibilities that must be maintained, especially regarding children's rights. In line with Law Number 23 of 2002 concerning Child Protection, parents have primary obligations, including caring for, nurturing, educating and protecting children. This thesis explains that after divorce, children become direct victims by being separated from their parents. Child care, especially the cost of the hadhanah, is the father's responsibility according to the Compilation of Islamic Law Article 156 letter d. However, if parents do not fulfill their obligations, child custody rights can be revoked at the request or coercion of the court